PEMBUATAN TEPUNG TANAMAN SIKAS (Cycas rumpii) SEBAGAI SUMBER MAKANAN - Rumodar, Sehat; Tuaputty, Hasan; Parry, Cornelia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Utilization of flour (carbohydrate) from the Cycas rumpi plant by the community in Amarsekaru Village, Gorom Island District, Eastern Seram Regency, according to the frequency and percentage, the results of the analysis show (1) Cycas rumpi plants are easy to obtain according to the respondents' answers 86.7% (2) Consuming keu 90.9% of respondents stated that it was safe for consumption and did not cause harm to the body (3) Only 80% of people who could make flour (carbohydrates) from the Cycas rumii plant (4) produced flour (carbohydrates) 73.3% sold it directly for their living needs, (5) From the respondents' answers, 73.3% of the people could make various types of cakes from Cycas rumii flour (6) 66.7% of the people who ate cakes made from Cycas rumii flour. The results of the analysis of the food (cake) taste test from Cycas rumpii flour showed the following: (1) The smell or smell of the food (cake) with good to very good criteria was 90.9%, (2) The delicacy of the food (cake) from Cycas rupii flour respondents' answers with very good criteria to good criteria were 81.8%, delicacy answers with quite good criteria to 18.2% unfavorable criteria. (3) The cakes taste from Cycas rumii flour with good to very good criteria was 100%, (4) The cake color with good to very good criteria was 63.6%, (5) The cake texture from Cycas rumii flour was based on good criteria to very good at 90.9%. Keywords: Flour, Cycas rumpii, Food